Comparison of human glomerulus proteomic profiles obtained from low quantities of samples by different mass spectrometry with the comprehensive database - Liu Zan; Fujinaka Hidehiko; Magdeldin Sameh; Xu Bo; Yoshida Yutaka; Zhang Ying; Miyamoto Masahito; Yaoita Eishin; Yamamoto Tadashi (Proteome Science, 2011)
Abstract Background We have previously constructed an in-depth human glomerulus proteome database from a large amount of sample for understanding renal disease pathogenesis and aiding the biomarker exploration. However, it is usually a challenge for clinical research to get enough tissues for large-scale proteomic characterization. Therefore, in this study, we focused on high-confidence proteomics analysis on small amounts of human glomeruli comparable to those obtained from biopsies using different mass spectrometers and compared these results to the comprehensive database. Results One microgram of human glomerular protein digest was analyzed each on five LC- combined mass spectrometers (LIT-TOF, LTQ-Orbitrap, Q-TOF, LIT and MALDI-TOF/TOF) yielding 139, 185, 94, 255 and 108 proteins respectively identified with strict criteria to ensure high confidence (> 99%) and low false discovery rate (FDR) (< 1%). An integrated profile of 332 distinct glomerular proteins was subsequently generated without discerned bias due to protein physicochemical properties (pI and MW), of which around 60% were detected commonly by more than two LC-MS/MS platforms. Comparative analysis with the comprehensive database demonstrated 14 proteins uniquely identified in this study and more than 70% of identified proteins in small datasets were concentrated to the top abundant 500 in the comprehensive database which consists of 2775 non-redundant proteins. Conclusion This study showed representative human glomerulus proteomic profiles obtained from biopsies through analysis of comparable amounts of samples by different mass spectrometry. Our results implicated that high abundant proteins are more likely to be reproducibly identified in multiple mass spectrometers runs and different mass spectrometers. Furthermore, many podocyte essential proteins such as nephrin, podocin, podocalyxin and synaptopodin were also identified from the small samples in this study. Bioinformatic enrichment analysis results extended our understanding of the major glomerular proteins about their subcellular distributions and functions. The present study indicated that the proteins localized in certain cellular compartments, such as actin cytoskeleton, mitochondrial matrix, cell surface, basolateral plasma membrane, contractile fiber, proteinaceous extracellular matrix and adherens junction, represent high abundant glomerular proteins and these subcellular structures are also highly significantly over-represented in the glomerulus compared to the whole human background.